The Imperial Russian Army in Peace, War, and Revolution, 1856-1917 - Reese, Roger R. (Book collections on Project MUSE., 2019)
"This book is a social history of the Russian Army of the late imperial period that exposes the myths and corrects misinformation and misconceptions that have grown up around the history of the Imperial Russian Army. Through the use of recently available primary sources, Roger Reese demonstrates that the existing works of history provide a one-sided view of army life from the perspective of the most conservative officers, who were ignorant to the reality of the soldiers' lives. Reese argues that the existing explanations for the collapse of the Imperial Russian Army are either inadequate or inaccurate: World War One itself was not the only catalyst for the army's collapse; the officer corps failed to learn from the 1905 Revolution, which gave them all the information that they needed to avoid another revolt by soldiers; and the mutinies of the soldiers and heightened disaffection of Russian society in general should have been a wake-up call for the military to drastically change the relationship between officers and men, yet it went unheeded."